Studi Perancangan Instalasi Pengolahan Air Limbah (IPAL) Domestik di Desa Butuh, Kecamatan Butuh, Kabupaten Purworejo - Anggie Herlambang Ainul Yaqien Machsuni Hadi; Budi Utomo; Koosdaryani Soeryodarundio (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Butuh Village is one of the villages in Butuh District, Purworejo Regency, Central Jawa Province. The villages’s need for awareness of adequate sanitation is still quite low. This can be proven by the fact that there are still many houses that do not have adequate domestik waste processing infrastructure. AS we know, if we dispose of domestik waste in the form of grey water and black water directly into the environment without a good waste processing system, it will pollute the environmen. The aim of this design is to determine the domestik wastewater treatment bulding in Butuh village using the hierarchical method.The final calculation using the hierarchical method resulted in thr selected domestic wastewater treatment being the Anaerbic Buffled Reactor (ABR) using 4 parameters in the form of maintenance operatinal cost, land area used, construction costs and removal efficiency. The Anaerobic Buffled Reactor (ABR) is planned to have 5 compartments with a BOD removal efficiency of 84%, construction cost of Rp. 67.899.607, the land area required is 45 m2, and operational costs are Rp. 2.605.281 and maintenance is relatively easy.